2016
DOI: 10.1038/srep25035
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction between V-ATPase B2 and (Pro) renin Receptors in Promoting the progression of Renal Tubulointerstitial Fibrosis

Abstract: To investigate the levels of (Pro) renin receptor [(P) RR], α-smooth muscle actin (α-SMA), fibronectin (FN), and vacuolar H+-ATPase (V-ATPase) subunits (B2, E, and c) in rat unilateral ureteral obstruction (UUO) models and rat proximal tubular epithelial cells (NRK-52E) treated with prorenin to elucidate the role of V-ATPase in these processes by activating the (P) RR. UUO significantly upregulated (P) RR, V-ATPase subunits, α-SMA and FN expression in tubulointerstitium or tubular epithelial cells. A marked co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…105 Whereas PRR activation of the Wnt/b-catenin signaling was independent of prorenin in the aforementioned study, 105 others report that prorenin treatment in cultured renal tubular epithelial cells, albeit at higher doses than seen in vivo, enhances expression of the PRR, vacuolar H þ -ATPase, and profibrotic markers. 106,107 Further, inhibition of the PRR or vacuolar H þ -ATPase activity partially reduced prorenin-induced fibronectin and asmooth muscle actin expression, suggesting that prorenin, via the PRR, promotes renal fibrosis. 106 However, mice with constitutive global overexpression of PRR did not manifest cardiac or renal fibrosis despite marked increases in renal and cardiac PRR expression.…”
Section: Role Of the (Pro)renin Receptor In Fibrosismentioning
confidence: 96%
See 1 more Smart Citation
“…105 Whereas PRR activation of the Wnt/b-catenin signaling was independent of prorenin in the aforementioned study, 105 others report that prorenin treatment in cultured renal tubular epithelial cells, albeit at higher doses than seen in vivo, enhances expression of the PRR, vacuolar H þ -ATPase, and profibrotic markers. 106,107 Further, inhibition of the PRR or vacuolar H þ -ATPase activity partially reduced prorenin-induced fibronectin and asmooth muscle actin expression, suggesting that prorenin, via the PRR, promotes renal fibrosis. 106 However, mice with constitutive global overexpression of PRR did not manifest cardiac or renal fibrosis despite marked increases in renal and cardiac PRR expression.…”
Section: Role Of the (Pro)renin Receptor In Fibrosismentioning
confidence: 96%
“…106,107 Further, inhibition of the PRR or vacuolar H þ -ATPase activity partially reduced prorenin-induced fibronectin and asmooth muscle actin expression, suggesting that prorenin, via the PRR, promotes renal fibrosis. 106 However, mice with constitutive global overexpression of PRR did not manifest cardiac or renal fibrosis despite marked increases in renal and cardiac PRR expression. 45 Interpretation of these findings is difficult; however, the bulk of evidence suggests that the PRR, at least under some conditions, may play a profibrotic role.…”
Section: Role Of the (Pro)renin Receptor In Fibrosismentioning
confidence: 96%
“…Therefore, the binding of prorenin to PRR stimulates V‐ATPase and subsequent promotes ERK1/2 phosphorylation, this may be a mechanism prorenin‐induced fibrosis in cultured renal cells. To support this notion, siRNA‐mediated PRR or V‐ATPase B2 subunit knockdown partially decreased V‐ATPase activity and inhibited prorenin‐induced α‐smooth muscle actin and fibronectin expression in NRK‐52E cells 148 . What's more, podocyte‐specific PRR knockout mice developed severe kidney failure and proteinuria, and mice with inducible renal tubule‐specific deletion of PRR displayed distal renal tubular acidosis, both the phenotypes were as a result of V‐ATPase dysfunction and impaired autophagy independently of RAS 20,149‐152 .…”
Section: Prr Work As An Accessory Subunit Of the Vacuolar H+‐atpase mentioning
confidence: 98%
“…Within the kidney, PRR is co‐localized with the V‐ATPase in the podocytes, proximal tubules, and intercalated cells of CDs 13,14 . Although it has been reported that the binding of prorenin to PRR was dispensable for the biogenesis of active V‐ATPase in mouse embryonic fibroblast cultures, 136 and luminal application of prorenin did not acutely stimulate V‐ATPase activity isolated cortical CDs, 14 several studies have reported that prorenin stimulated V‐ATPase activity dependently of PRR but not Ang II in MDCK.C11 CD cells 147 and rat proximal tubular epithelial cells (NRK‐52E) 148 . PRR depletion abolished both prorenin‐ and AVP‐ induced stimulation of V‐ATPase activity, suggesting that PRR is required for prorenin‐dependent and ‐independent stimulation of V‐ATPase activity in the CDs 147 .…”
Section: Prr Work As An Accessory Subunit Of the Vacuolar H+‐atpase mentioning
confidence: 99%
See 1 more Smart Citation